HSP90 promotes Burkitt lymphoma cell survival by maintaining tonic B-cell receptor signaling - Walter, Roland; Tomska, Katarzyna; Zenz, Thorsten; Oellerich, Thomas (Blood, 2017)
Burkitt lymphoma (BL) is an aggressive B-cell neoplasm that is currently treated by intensive chemotherapy in combination with anti-CD20 antibodies. Because of their toxicity, current treatment regimens are often not suitable for elderly patients or for patients in developing countries where BL is endemic. Targeted therapies for BL are therefore needed. In this study, we performed a compound screen in 17 BL cell lines to identify small molecule inhibitors affecting cell survival. We found that inhibitors of heat shock protein 90 (HSP90) induced apoptosis in BL cells in vitro at concentrations that did not affect normal B cells. By global proteomic and phosphoproteomic profiling, we show that, in BL, HSP90 inhibition compromises the activity of the pivotal B-cell antigen receptor (BCR)-proximal effector spleen tyrosine kinase (SYK), which we identified as an HSP90 client protein. Consistently, expression of constitutively active TEL-SYK counteracted the apoptotic effect of HSP90 inhibition. Together, our results demonstrate that HSP90 inhibition impairs BL cell survival by interfering with tonic BCR signaling, thus providing a molecular rationale for the use of HSP90 inhibitors in the treatment of BL.
First edition: November 15, 2016
Gesehen am 14.11.2018